Consequences of Emigration from Moldova - Bubuioc, Rodica (2012)
The aim of this thesis is to analyze the consequences of emigration from Moldova including its forms, causes, risks and consequences of the population development. The first chapter provides introductive information about Moldova, its statistical-demographical indicators and overview of the demographical development. The second chapter proceeds with a detailed information about the emigrational trends, as well the individual approaching forms of estimating the emigration. The third chapter focuses on the demographic, economic and social impact of the phenomena explained in chapter two, mostly concentrated on the labor migration which represents the main component of the Moldovan temporary emigration.